2015
DOI: 10.1038/ijir.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment expectations of men with ED and their female partners: an exploratory qualitative study based on grounded theory

Abstract: Erectile dysfunction (ED) can impair the quality of life and the relationship. An early treatment is necessary to avoid the development of comorbid complaints. To arise the help-seeking behavior and to improve the treatment of affected men, it is necessary to be aware of the treatment expectations. The objective of this study was to investigate the treatment expectations of men with ED and their female partners. This is an explorative qualitative study using semistructured telephone interviews with 12 men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…[6][7][8] Embarrassment and disbeliefs regarding treatment among the patients, improper expertise of health providers and hostile atmosphere in the health institutions has been often implicated in deficiency of treatment seeking behavior among patients of ED. 9,10 As such, a thorough work-up including elicitation of risk factors coupled with necessary laboratory tests and integrated with clinical picture helps to diagnose and develop a treatment plan to manage these patients effectively. 11 Different protocols of diagnosis and treatment have always been the matter of interest for clinicians worldwide with the problem still showing a significant prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Embarrassment and disbeliefs regarding treatment among the patients, improper expertise of health providers and hostile atmosphere in the health institutions has been often implicated in deficiency of treatment seeking behavior among patients of ED. 9,10 As such, a thorough work-up including elicitation of risk factors coupled with necessary laboratory tests and integrated with clinical picture helps to diagnose and develop a treatment plan to manage these patients effectively. 11 Different protocols of diagnosis and treatment have always been the matter of interest for clinicians worldwide with the problem still showing a significant prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the findings of our study indicate that most men living with DED have concerns about their social relationships, especially marriage. Erectile problems also cause a problem with their role as a husband, since they cannot satisfy their partners' desires [13,14,29]. This is further evidence that men who have erectile difficulty need support and understanding about their sex lives from both their partners and their health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…This could relate to the duration of having DED and self-adjustment, as mild DED is generally seen in the early stages of erectile difficulty [28]. Subjects in the early stages of erectile difficulty may need to cope with a notable decrease in their sexual performance, as well as a perceived loss of manhood and gender role, e.g., the role of husband [16,29]. Perhaps this could explain why it is associated with reduced QoL, as they could not sexually satisfy their partners [30], whereas those who have more severe DED are familiar and have more experience adjusting to their impotence, as DED is a chronic condition that develops over time [31].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 , 18 , 19 , 22 ] Studies on barriers to seeking help have identified, for instance, perceptions that ED is a normal effect of ageing [ 23 ] and that the physician would dismiss sexual difficulties as trivial. [ 24–25 ] In our study, we asked for motives for actually seeking help, rather than what hinders it. Fear of illness was one important reason, which has previously not received much attention in primary health care.…”
Section: Discussionmentioning
confidence: 99%